2013
DOI: 10.1002/ange.201207855
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Magnetic Bistability of Mn3O4 Nanoparticles Encapsulated in Hollow Carbon Nanofibers

Abstract: Unter Verschluss: Magnetische Nanopartikel wurden in hohlen Kohlenstoffnanofasern eingeschlossen. Dichte und Orientierung der Mn3O4‐Nanopartikel hängen von der inneren Struktur des Kohlenstoff‐Nanocontainers ab, was eine Feinabstimmung der magnetischen Eigenschaften des Kompositmaterials ermöglicht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…7). The study by Del Carmen Gimenez-Lopez et al [4] also showed that larger nanobricks were encapsulated when CNFs were used, over GNF (see Fig. 7).…”
Section: Encapsulation Of Metals In Cntsmentioning
confidence: 76%
See 4 more Smart Citations
“…7). The study by Del Carmen Gimenez-Lopez et al [4] also showed that larger nanobricks were encapsulated when CNFs were used, over GNF (see Fig. 7).…”
Section: Encapsulation Of Metals In Cntsmentioning
confidence: 76%
“…However, a considerable advantage of the assimilation of packed metal oxides in the CNFs was their higher packing density (26 % vs. 11 %) than in GNFs. The study by Del Carmen Gimenez-Lopez et al [4] showed that the most magnetic material was the CNF composite, given its higher packing density of metaloxide (see Fig. 7).…”
Section: Encapsulation Of Metals In Cntsmentioning
confidence: 94%
See 3 more Smart Citations